Comparison of Sufentanil- and Fentanyl-based Intravenous Patient-controlled Analgesia on Postoperative Nausea and Vomiting after Laparoscopic Nephrectomy: A Prospective, Double-blind, Randomized-controlled Trial - Lee, Hye-Mi (Int J Med Sci, 2020)
Background: The incidence of postoperative nausea and vomiting (PONV) remains high. The effects of sufentanil for PONV is not firmly confirmed. The aim of this study was to compare the effect of sufentanil- and fentanyl-based intravenous patient-controlled analgesia (IV-PCA) on the incidence of PONV after laparoscopic nephrectomy. Methods: Eighty-six patients were randomly allocated to receive either the sufentanil (n =43) or fentanyl (n =43). IV-PCA was prepared using either sufentanil 3 µg/kg or fentanyl 20 µg/kg, ramosetron 0.3 mg, and ketorolac 120 mg. The primary outcome of was the incidence of PONV during 24 h after post anesthesia care unit (PACU) discharge. The secondary outcomes were the modified Rhodes index and patient satisfaction scores at 24 h after PACU discharge, need for rescue antiemetics, pain score, need for additional analgesics, and cumulative consumption of IV-PCA Results: The incidence of PONV was comparable between the sufentanil and fentanyl groups (64.3% vs. 65%, p = 0.946; respectively). The number of patients who required antiemetics (p = 0.946) and the modified Rhodes index at 24 h after post-anesthesia care unit discharge (p = 0.668) were also comparable in both groups. No significant differences were found in the secondary outcomes, including the analgesic profiles and adverse events between the groups. Conclusions: In conclusion, sufentanil- and fentanyl-based IV-PCA showed similar incidence of PONV with comparable analgesic effects after laparoscopic nephrectomy. Based on these results, we suggest that sufentanil and fentanyl may provide comparable effects for IV-PCA after laparoscopic nephrectomy.